The voice over : poems and essays - Stepanova, Marii͡a (Russian library (Columbia University. Press), 2021)
"Maria Stepanova is one of the most powerful and distinctive voices of Russia's first post-Soviet literary generation. An award-winning poet and prose writer, she has also founded a major platform for independent journalism. Her verse blends formal mastery with a keen ear for the evolution of spoken language. As Russia's political climate has turned increasingly repressive, Stepanova has responded with engaged writing that grapples with the persistence of violence in her country's past and present. Some of her most remarkable recent work as a poet and essayist considers the conflict in Ukraine and the debasement of language that has always accompanied war. The Voice Over brings together two decades of Stepanova's work, showcasing her range, virtuosity, and creative evolution. Stepanova's poetic voice constantly sets out in search of new bodies to inhabit, taking established forms and styles and rendering them into something unexpected and strange. Recognizable patterns of ballads, elegies, and war songs are transposed into a new key, infused with foreign strains, and juxtaposed with unlikely neighbors. As an essayist, Stepanova engages deeply with writers who bore witness to devastation and dramatic social change, as seen in searching pieces on W. G. Sebald, Marina Tsvetaeva, and Susan Sontag. Including contributions from ten translators, The Voice Over shows English-speaking readers why Stepanova is one of Russia's most acclaimed contemporary writers"--